Ценностные параметры современной русской лексикографии - Kozyrev, Vladimir; Cherniak, Valentina (Wiener Slawistischer Almanach, 2023)
The article discusses axiologically loaded value parameters in lexicography, in particular the role of the name of a dictionary and its significance for the development of lexicography. A general picture of the lexicographic space under review, its center and its periphery, was constructed using material from 3,600 dictionaries of the Russian language. Axiologically-loaded parameters in a name of a dictionary (new, modern, large, full, short, pocket, for everyone, etc.) correlate with evaluative stereotypes, but often do not reflect the essential characteristics of the dictionary and are used only to attract the user’s attention. This explains the existence of a large number of lexicographic fakes. Value parameters largely determine the strategies not only of the authors, but also of the publisher. The true value of a lexicographic publication can be determined from a scientific and substantive perspective, as well as from the perspective of the purely pragmatic user.